TRENDS IN THE DEVELOPMENT OF FINANCIAL MANAGEMENT ACCORDING TO THE CONCEPTS OF INDUSTRY AND MANAGEMENT 4.0 - KUDLAENKO, SERGEY (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The development of financial management at all levels of the economy ensures targeted, efficient and effective financial management, the stability of financial flows of the economic landscape of an enterprise (institution), region, state, enterprise, individual projects. The implemented rational financial management allows optimal allocation and use of resources; carry out strategic and tactical planning and implement systems for monitoring the use of resources; make informed investment decisions; manage risks; to form quality reports; promote economic growth and maintain financial security. In the conditions of digitalization, financial management uses modern management and communication technologies. The issue of tracking trends in the development of financial management is an urgent task not only for financiers and business owners, but also for top managers and investors Financial management of the enterprise is one of the components of the success of sustainable development. Tracking trends in the development of financial management and introducing changes in the management of cash and investment flows with the help of modern management and digital technologies are urgent tasks for obtaining financial results in accordance with the strategic goals of the company’s development. The issue of tracking trends in the development of financial management is an urgent task not only for financiers and business owners, but also for top managers and investors. The scale of the enterprise involves the formation of financial indicators as key measures of activity results in accordance with the enterprise’s development strategy. Modern strategies provide for the development of innovativeness, sustainable growth, and social responsibility. The concepts of the development of modern enterprises and their management testify to the introduction of modern information technologies, artificial intelligence, analytical tools, forecasting, etc. The identified trends in the development of financial management and the step-by-step creation of a road map will allow determining the main directions of financial control, introducing changes, and making a reasonable choice of options for optimizing cash and investment flows.